The new international Webster's pocket dictionary of the English language - Bailey, Eileen (United States : Trident Press International, 1998)
1. English language -- Dictionaries.
"Entries taken from Webster Contemporary Dictionary, illustrated edition"--T.p. verso.
Basic ed. students
Keywords: English language -- Dictionaries